(untitled) (American Journal of Islam and Society, 2005)
Some scholars, such as Graham Fuller, tend to read the current experiment in Turkey as the successful political integration of an Islamic movement into a democracy.1 Several facts support such an interpretation. Although the JDP [Justice and Democracy Party] leadership denies its Islamic background and claims to be a conservative democratic party, nonetheless, the party did emerge out of the ashes of the Welfare [Refah] and the Virtue [Fazilet] parties that were closed down by the constitutional court on charges of being a forum for and proponent of anti-secular activities.2 Moreover, the majority of JDP’s deputies are observant Muslims in their daily lives. For instance, their spouses continue to wear headscarves, which are banned in public offices, state ceremonies, and universities because they are regarded as a threat to Turkey’s secular character. The religious observance of JDP’s members poses several questions. Is the JDP an Islamic party? Is it possible for an ex-Islamic movement to become a-Islamic or un- Islamic? Is the commitment of the JDP’s members to religious values in their personal life sufficient to label the party Islamic? When does a movement or a party become or cease to be Islamic? Even if the party’s administration denies any connection with political Islam, can we still consider the party to be Islamic? Alternatively, one may argue that JDP’s denial of being an Islamic party is simply a compromise between the state and the JDP. The party, as the argument goes, is free to govern the country as long as it stays within Turkey’s strictly proscribed constitutional framework and ignores many of its conservative constituency’s religious demands. This alternative interpretation further complicates the issue and raises following question: Is the JDP, rather than being the success story of an Islamic movement that has adapted to a democratic and secular environment, an example of the ...